The Use of Online Marketplace Website in Indonesia: A Study of Consumers’ Motives and Gratification - Humaizi, Humaizi; Asmara, Sakhyan; Sis, Rany Listiawati; Yusuf, Muhammad (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The rapid development of technology eases people to do many things such as shopping, paying bill, transferring money, and so on. This study is intended to discover consumers’ motives and gratifications in using online marketplace website through uses and gratification theory (UGT). This study employed quantitative method. The population in this study is the undergraduate students’ of business and economy faculty of Universitas Sumatera Utara who have ever made a purchase at tokopedia.com and bukalapak.com. Accidental and purposive samplings were utilized to determine the samples totaling to 66 respondents. The methods employed to collect the data were survey and questionnaire. Validity and reliability was tested by using SPSS 17.0 Program, and to test the significance level, t-test was employed. The results elucidate the users’ got gratified in information, entertainment, and social interaction motives. Meanwhile, in economic and convenience motives, the users’ gratification was not achieved. Then, there is no difference in the gratification level of Tokopedia.com and Bukalapak.com users. The discrepancy level between motives and users’ gratification in the information, comfortability, entertainment, social interaction, and economic dimension yields not significant score.